Researching Education with Marginalized Communities - Danaher, M. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This collection provides evidence-based strategies for conducting effective and ethical education research with individuals and groups who are marginalised from mainstream society. The book explores circus and fairground communities, disabled vocational education students, environmental lobbyists and retired people from across the globe.